Computational analysis of spliced leader trans-splicing in the regenerative flatworm Macrostomum lignano reveals its prevalence in conserved and stem cell related genes - K. V. Ustyantsev; E. V. Berezikov (Вавиловский журнал генетики и селекции)
In eukaryotes, trans-splicing is a process of nuclear pre-mRNA maturation where two different RNA molecules are joined together by the spliceosomal machinery utilizing mechanisms similar to cis-splicing. In diverse taxa of lower eukaryotes, spliced leader (SL) trans-splicing is the most frequent type of trans-splicing, when the same sequence derived from short small nuclear RNA molecules, called SL RNAs, is attached to the 5’ ends of different non-processed pre-mRNAs. One of the functions of SL trans-splicing is processing polycistronic pre-mRNA molecules transcribed from operons, when several genes are transcribed as one pre-mRNA molecule. However, only a fraction of trans-spliced genes reside in operons, suggesting that SL trans-splicing must also have some other, less understood functions. Regenerative flatworms are informative model organisms which hold the keys to understand the mechanism of stem cell regulation and specialization during regeneration and homeostasis. Their ability to regenerate is fueled by the division and differentiation of the adult somatic stem cell population called neoblasts. Macrostomum lignano is a flatworm model organism where substantial technological advances have been achieved in recent years, including the development of transgenesis. Although a large fraction of genes in M. lignano were estimated to be SL trans-spliced, SL trans-splicing was not studied in detail in M. lignano before. Here, we performed the first comprehensive study of SL trans-splicing in M. lignano. By reanalyzing the existing genome and transcriptome data of M. lignano, we estimate that 30 % of its genes are SL trans-spliced, 15 % are organized in operons, and almost 40 % are both SL trans-spliced and in operons. We annotated and characterized the sequence of SL RNA and characterized conserved cis- and SL transsplicing motifs. Finally, we found that a majority of SL trans-spliced genes are evolutionarily conserved and signif icantly over-represented in neoblast-specific genes. Our findings suggest an important role of SL trans-splicing in the regulation and maintenance of neoblasts in M. lignano.